E-learning, assessment competency, and academic performance: A structural equation modeling approach - Nor Hasnida binti Che Md Ghazali, Zahari bin Suppian, Hishamuddin Bin Ahmad, Syaza Hazwani binti Zaini, Tajul Rosli bin Shuib (Tanjung Malim, 2024)
E-learning, assessment competency, and academic performance: A structural equation modeling approach by Nor Hasnida binti Che Md Ghazali, Zahari bin Suppian, Hishamuddin Bin Ahmad, Syaza Hazwani binti Zaini, Tajul Rosli bin Shuib